Quality structuring of medical services by decomposition of quality function - Mykyichuk, Mykola; Chaban, Olesia (Видавництво Львівської політехніки, 2020)
Quality medical care is an important indicator of the economic development of a country. Today, improving the quality of health care services is a priority for both health care institutions and the state as a whole. The development of methods and tools for continuous improvement of the quality of medical services promotes regulation, the perfection of those services, ensures the effective working of all the components together and the consistency and continuity of their provision, as well as help the staff to determine how to achieve the optimal level of care. The implementation of modern methods of ensuring the quality of products and services in medical practice is aimed at increasing patient satisfaction and receiving adequate and professional medical care, in accordance with the principles of Good Clinical Practice. Therefore, it is important to summarize and systematize the requirements for healthcare delivery processes. A key element of the quality management model of care is a process analysis, which involves the identification and design of processes along with their continual improvement. At the same time, the result of management is based on a cycle of actions aimed at minimizing the frequency of deviations in key processes, which guarantees the achievement of the best potential scientifically verified results. There are several groups of processes in a medical institution: treatment, diagnostics, supply, etc. Defining the function of the quality of medical services and their decomposition will allow for optimizing the work of medical institutions and encourage efficiency and competitiveness in innovative development. The article presents the scheme of optimization of medical services by decomposition of their function of quality. A graphic model of decomposition of the function of the quality of health services is proposed based on the model of relations which will formalize the requirements for the processes of providing medical services in a medical institution. This will help to provide healthcare services gradually and minimize the loss of quality of the provided medical services.
Keywords: Medical services; Process of optimization; Mathematical model; Quality function